Development of Virlenda-Based Blended Learning with Problem Based Learning Strategy for Problem-Solving Ability for Students - Achmad Noor Fatirul; Subandowo Subandowo (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This study aims to develop a Virlenda-based blended learning model. The products that will be produced develop learning tools with problem-based learning strategies, problem-based evaluation tools, supplements for lecturers and students and the Virlenda learning management system as a forum for carrying out the learning process. The results of the research are design experts with 85.8% validation percentage, material experts with 86.5 validation percentages, media experts with 87.7% validation percentages, 86.5% validation percentages for colleagues. In the small group trial the percentage of responses was 82.7%, for the medium group trial the percentage of responses was 89.6%, while in the large group trial the percentage was 92%. The results of the products developed can be used as guidelines in the learning process, so that products can be mass-produced to be distributed to universities. In the field group trial comparing the old model and the new model, it got 0.458 for Google Classroom and 0.916 for Virlenda, so Virlenda is significantly better than Google Classroom.Abstrak: Penelitian ini bertujuan untuk mengembangkan model blended learning berbasis Virlenda. Produk yang akan dihasilkan mengembangkan perangkat pembelajaran dengan strategi pembelajaran berbasis masalah, perangkat evaluasi berbasis masalah, suplemen untuk dosen dan mahasiswa serta sistem manajemen pembelajaran Virlenda sebagai wadah untuk melaksanakan proses pembelajaran. Hasil penelitian adalah ahli desain dengan persentase validasi 85,8%, ahli materi dengan persentase validasi 86,5, ahli media dengan persentase validasi 87,7%, dan rekan sejawat 86,5%. Pada uji coba kelompok kecil persentase tanggapannya adalah 82,7%, untuk uji coba kelompok sedang persentase tanggapannya adalah 89,6%, sedangkan pada uji coba kelompok besar persentasenya adalah 92%. Hasil produk yang dikembangkan dapat dijadikan pedoman dalam proses pembelajaran, sehingga produk dapat diproduksi secara massal untuk didistribusikan ke perguruan tinggi. Dalam uji coba kelompok lapangan yang membandingkan model lama dan model baru didapat 0,458 untuk Google Classroom dan 0,916 untuk Virlenda. Jadi, Virlenda secara signifikan lebih baik daripada Google Classroom.